The Place of Rivers in the Colonial Economy of Nigeria - Ongele, Festus Nwankwo (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2024)
Nigeria is one of the countries in Africa that are strategically positioned, and blessed with many rivers. Rivers Niger and Benue are the two major rivers in Nigeria.  Other common ones include River Imo, River Anambra, Kaduna River, and River Ogun. It is discovered that these rivers and their tributaries played significant roles in the growth and development of Nigerian economy under colonial rule. They equally facilitated the European imperialistic activities in the area. Further investigations revealed that the essence of these rivers manifested in the areas of agriculture, industry, trade and commerce, and strategic importance. They essentially, served as tourist centres, fishing areas, means of transport and sources of water for irrigation. This paper argues that without navigable rivers, streams and creeks which served as, among other things, transport routes that linked different parts of Nigerian, the sectors of the country’s economy and the European economic interest could have suffered severe setbacks. The work relied on both primary and secondary sources. Its data were analyzed qualitatively according to contents.